Changes in center of pressure displacement with the use of a foot drop stimulator in individuals with stroke. Issue 7 (August 2015) - Nolan, Karen J.; Yarossi, Mathew; Mclaughlin, Patrick
Abstract: Background: Center of pressure measured during gait can provide information about underlying control mechanisms and the efficacy of a foot drop stimulator. This investigation evaluated changes in center of pressure displacement in individuals with stroke with and without a foot drop stimulator. Methods: Individuals with stroke-related foot drop (n = 11) using a foot drop stimulator and healthy controls (n = 11). Walking speed and bilateral center of pressure variables: 1) net displacement; 2) position and maximum displacement; and 3) mean velocity during walking. Findings: On the affected limb with the foot drop stimulator as compared to the affected limb without the foot drop stimulator: 1) increased anterior/posterior maximum center of pressure excursion 8% during stance; 2) center of pressure at initial contact was 6% more posterior; 3) medial/lateral mean, maximum and minimum center of pressure position during stance all significantly decreased; 4) anterior/posterior net displacement increased during stance and single support; and 5) anterior/posterior velocity of the center of pressure increased during stance. Interpretation: Individuals with stroke using a foot drop stimulator contacted the ground more posterior at initial contact and utilized more of the anterior/posterior plantar surface of the foot on the affected limb during stance. With the foot drop stimulator there was a shift in center of pressure toward the medial side possibly indicating an improvement in equinovarus gait where there is a tendency to load the lateral foot throughout stance. For individuals with stroke a foot drop stimulator can improve displacement of the center of pressure which indicates improved forward progression and stability during walking. Highlights: Center of pressure displacement during walking was measured with and without a foot drop stimulator. Participants were individuals with foot drop secondary to stroke and healthy controls. Center of pressure progression within the sub phases of stance was used to evaluate changes in gait mechanics and gait quality. For individuals with stroke, a foot drop stimulator can improve forward progression and stability.